Menopause mysteries: the exosome-inflammation connection - Aarushi Sultania; Subhashini Brahadeeswaran; Aparna Eledath Kolasseri; Sivaraman Jayanthi; Ramasamy Tamizhselvi (Journal of Ovarian Research)
Abstract Extracellular vesicles, or exosomes, are produced by every type of cell and contain metabolites, proteins, lipids, and nucleic acids. Their role in health and disease is to influence different aspects of cell biology and to act as intermediaries between cells. Follicular fluid exosomes or extracellular vesicles (FF-EVs) secreted by ovarian granulosa cells are critical mediators of ovary growth and maturation. The movement and proteins of these exosomes are crucial in the regulation of cellular communication and the aging of cells, a process termed inflammaging. Menopause, a natural progression in the aging of females, is often accompanied by numerous negative symptoms and health issues. It can also act as a precursor to more severe health problems, including neurological, cardiovascular, and metabolic diseases, as well as gynecological cancers. Researchers have discovered pathways that reveal the diverse effects of exosome-driven cellular communication and oocyte development in the follicular fluid. It also explores the complex functions of FF exosomal proteins in the pathologies associated with menopause. Graphical Abstract